Capacity performance of steganography method in text based domain - Osman, Baharudin; Din, Roshidi; Idrus, Mohd Rushdi (Asian Research Publishing Network (ARPN), 2015)
Capacity is one of the performance factors in embedding process of any text steganography methods.A better embedding ratio and saving space ratio offers more text can be hidden inside cover text.This paper tries to evaluate several format based techniques of text steganography based on their embedding ratio and saving space capacity factors.This paper analysed the performance of text steganography methods which are changing in Alphabet Letter Patterns (CALP), Vertical Straight Line (VERT) and Quadruple Categorization (QUAD) methods based on these two factors.Embedding Ratio (ER) and Saving Space Ratio (SSR) is used to measure the performance.It has been identified that VERT method give a good effort performance compared to CALP and QUAD based method.In future, a robustness of text steganography methods should be considered as a next effort in order to find a strength capability on text steganography.